Recruiting and Retaining Young Urban Black Men in a Study of Violence: Procedures Used and Lessons Learned. Issue 2 (May 2019) - Leech, Tamara G. J.; Irby-Shasanmi, Amy; Sow, Hadya
We conducted a study about three common recruitment and retention obstacles facing scholars interested in racial disparities research: potential mistrust from the black community, a stigmatized research topic, and high participation burden. Nonetheless, we successfully recruited and retained 28 young black men in a three-month study of violence. In this article, we describe and explore the recruitment, engagement, and retention strategies employed during the study. Using a concurrent triangulation mixed-method design, we analyzed data from our web-based administrative system, participant enrollment and exit surveys, and team members' field notes. A large percentage (79%) of participants completed the study. We received 81% of 556 expected surveys, and 100% of the remaining participants wanted to continue participating at study's end. We conclude that internal incentives, the combination of informal and formal community recruiters, the visibility of the principal investigator, and face-to-face meetings may have contributed to the success of the project.